European LNG Import Network Analysis and Investigation of Supply Security - Konstantinos I. Savvakis; Tatiana P. Moschovou (Energies)
The shift of European countries to more environmentally friendly sources of energy is leading to an increase in the share of natural gas in the energy mix. At the same time, the flexibility and cost-effectiveness of maritime transport are making liquefied natural gas (LNG) more competitive compared to traditional forms of natural gas, despite recent geopolitical, health and economic events threatening its supply chain. The aim of this study is to analyze the European LNG import network using network theory indicators to identify trading communities in the network and to investigate the security of supply through network failure simulation. The network model was developed using a programming code in MATLAB R2022B software. The results of the analysis can be summarized as follows: (a) a shift in the center of gravity of LNG trade from the Mediterranean to the Atlantic shores was identified; (b) a gradual consolidation of Europe’s import network was noted; (c) an increasing dependence of Europe on a limited number of countries was observed; and (d) the most critical nodes for network resilience were identified through modeling. Based on these findings, recommendations are proposed to strengthen Europe’s energy security and independence.